Factors Associated with Sterile Syringe Acquisition among People Who Inject Drugs in West Virginia. (8th September 2021) - Allen, Sean T.; Mazhnaya, Alyona; O'Rourke, Allison; White, Rebecca Hamilton; Wedlock, Patrick; Grieb, Suzanne M.; Kilkenny, Michael E.; Walls, Melissa; Sherman, Susan G.
Abstract: Background: Syringe services programs (SSPs) are evidence-based interventions that provide essential overdose and infectious disease prevention resources to people who inject drugs (PWID). Little research has examined factors associated with sterile syringe acquisition at SSPs among rural PWID populations. Objectives: We aim to identify factors associated with PWID in a rural county in West Virginia having recently acquired sterile syringes at an SSP. Methods: PWID ( n  = 420) completed a survey that included measures related to sociodemographics, structural vulnerabilities, and substance use. We used multivariable Poisson regression with robust variance estimation to examine independent associations with sterile syringe acquisition at an SSP. Results: Sixty-five percent of our sample reported having recently acquired sterile syringes at an SSP. Factors associated with recent sterile syringes acquisition at an SSP included: being older (aPR [adjusted prevalence ratio]: 1.011, 95% CI: 1.003–1.019), single (aPR: 0.862, 95% CI: 0.755–0.984), experiencing food insecurity (aPR: 1.233, 95% CI: 1.062–1.431), recently injecting fentanyl (aPR: 1.178, 95% CI: 1.010–1.375) and prescription opioid pain relievers (aPR: 0.681, 95% CI: 0.551–0.842), and recent naloxone acquisition (aPR: 1.360; 95% CI: 1.178–1.569). Receptive syringe sharing was inversely associated with acquiring sterile syringes at an SSP (aPR: 0.852; 95% CI: 0.741–0.979). Conclusion: PWID accessing sterile syringes at an SSP was associated with several sociodemographic, structural, and substance use factors. Ensuring rural SSP operations are tailored to local PWID population-level needs is paramount to the prevention of infectious disease outbreaks and overdose fatalities.